Penegakan Diagnosa dan Tatalaksana Severe Dry Eyes pada Pasien Steven Johnson Syndrome - Aulia Nur Fitriatsani; Putu Ristyaning Ayu Sangging; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
Severe dry eyes or what can be called as severe dry eyes is a disease that is often encountered and could be happen to anyone. This disease is a multifactorial disease and is more common in women than men. Risk factors that can cause dry eyes are classified into several categories, namely individuals, environment, chronic disease, autoimmune disease, drugs, and history of injury. One of the factors that causes dry eyes, namely the use of drugs both topical and systemic drugs. The use of five or more drugs simultaneously can increase the risk of dry eyes. One disease that can trigger severe dry eyes in Steven Johnson Syndrome (SJS). SJS is a form of skin and mucous membrane disease caused by the body’s hypersensitivity reaction to a drug or infection. After the damage caused by the acute stage begins to subside, there will be severe visual disturbances and severe dry eyes. In the acute stage, ocular complications occur in 77% of SJS patients. Severe dry eyes can reduce the patient’s quality of life because it can interfere with vision, especially during daily activities. Severe dry eyes in SJS patients involve three important mechanisms, namely tear deficiency, decrease corneal surface moisture, and increase evaporation processes. Treatment of dry eyes can be given with artificial tears and stop using drugs that trigger dry eyes or replace drugs with other drugs. It is important to suppress chronic inflammation of the ocular surface and 2% rebamipide opthalmic solution can help restore stability to the ocular surface.. contact lenses can also be used to improve the patient’s visual acuity and reduce the symptoms associated with severe dry eyes.